Synthesis of Zeolite Based Material With Aluminum Sources from Used Beverage Cans for Hard Water Desalination - Muhammad Miqdam Musawwa; Nova Restu Nur Ardiyanto; Agil Lestari; Ahmad Khoiruddin Yusuf; Mochamad Solehudin (My University, 2022)
Hard water contains high mineral content, especially calcium (Ca) and magnesium (Mg). Hard water can cause health problems and damage to household appliances within a certain period of time. In this study, zeolite-based materials have been synthesized as adsorbent materials to reduce the concentration of Ca2+ and Mg2+ in the hard water obtained from Brondong district of Lamongan, East Java. Zeolite based material was synthesized with aluminum sources derived from beverage cans and silica from silica gel. In this study, zeolite was prepared by microwave (ZM) and without the microwave method (ZNM). The amount of ZM was 10.8121 grams, or 99.1% of the yield, and ZNM was 10.5387 grams or 99.15% of the yield. The FTIR results indicate some characteristic peaks of T-O and T-O-T bonds (T = Si/Al) at 460, 670, 726, and 980–1100 cm1. The diffractogram show that ZNM is still dominated by silica-based materials, while ZM although it still shows dominant amorphous silica peaks, some characteristic zeolite peaks also appear. The SEM results show the shapes of agglomerated tiny particles for both materials. In this study, the synthesized zeolite can reduce the concentration of Ca2+ ions by 84–97% and Mg2+ ions by 23-51%. The optimal time obtained in this study was 30 minutes, while the optimal mass obtained was 0.5 grams for all materials.
Keywords: null